Fertilizers and organic covers, slow release nutrient sources in the production of multiple harvest Swiss chard - Murga-Orrillo, Hipolito; Irigoin-Aguilar, Jhon Maber; Hilares-Vargas, Sharmely; Bardales-Lozano, Ricardo Manuel; Lobo, Francisco de Almeida (Revista de Ciências Agroveterinárias, 2019)
The objective of this study was to evaluate the performance of organic coverage and fertilizers on the production stability of Swiss chard. The experimental design was randomized blocks, in factorial arrangement and subdivided plots; using earthworm humus (A1), island guano (A2), and guinea pig manure (A3) as fertilizers, pine-leaf-sawdust (C1), rice husk (C2), and oat straw (C3) as covering, for three successive harvests. Percentage of emergence (E), length leaf (CF), fresh mass (MFF) weight, and dry mass (MSF) weight were evaluated. In the results, the coverages that provided the highest values were C2 and C3 with 43.1 and 42.7 cm in the CF, 209.9 and 215.5 g in the MFF, respectively; in fertilizers, A3 provided the highest values with 92.0% in E, 44.2 cm in CF, 231.6 g in MFF, and 154 g in MSF. The C2 and C3 coverages and the A3 fertilizer conditioned the best performances in the CF and MFF in relation to the other treatments; the yields remained in the 1st and 2nd harvest, dropping significantly in the 3rd harvest; humus from guinea pig manure presented detachable nutritional characteristics for use in horticulture.